Peningkatan Motorik Kasar Anak Usia 4-5 Tahun Melalui Permainan Tradisional Sondah Gunung (Engklek) - Mohammad Taufiq Aziz; Tia Susan (El-Mujtama: Jurnal Pengabdian Masyarakat, 2021)
Kindergarten (TK) or Raudatul Atfal (RA) children are generally very active, they have mastery over their bodies and really like doing activities on their own. Therefore, parents or teachers need to provide space and time for children to do activities that can train the child's gross muscles as well as provide items and equipment for children that can be pushed, lifted, thrown or carried. Teachers must also be creative in seeing learning models that can attract children's interest in learning. Traditional games are a wealth of the Indonesian nation. One of these types of traditional games, namely sondah gunung or crank, is a favorite game for children because it can be played by boys or girls. In the crank game there is a value for good physical development which is reflected in the crank game which requires whole body movements, namely lifting one leg, moving the body and hands. By doing these activities, it means that the child has carried out activities for sports, especially in gross motor movements, namely throwing, jumping, jumping, and standing on one leg. Apart from that, the mountain skating game can improve coordination and body balance and develop children's skills. All of which aim to help the child's growth. The implementation of gross motor learning activities for children aged 4-5 years with the traditional game of sondah gunung (crank) at RA Miftahul Jannah, Bogor City that has been implemented can significantly improve children's motor skills. The research was conducted with 1 pre-research activity and 2 research cycles with a total of 7 meetings. This is evidenced by an increase in the average in each assessment, namely in the pre-test the average motoric ability of children is 47.36%, then in cycle 1 it is 71.23% and in cycle 2 it is 86.54%. The average percentage increase from pretest to posttest in cycle 1 was 23.85%. The percentage of average increase from posttest in cycle 1 to posttest cycle 2 was 15.21%. So the average percentage increase from pretest to posttest cycle 2 is (23, 85% + 15, 21%) = 39, 06%.